Targeting senescent hepatocytes for treatment of metabolic dysfunction-associated steatotic liver disease and multi-organ dysfunction - Kuo Du; David S. Umbaugh; Liuyang Wang; Ji Hye Jun; Rajesh K. Dutta; Seh Hoon Oh; Niansheng Ren; Qiaojuan Zhang; Dennis C. Ko; Ana Ferreira; Jon Hill; Guannan Gao; et al. (Nature Communications)
Abstract Senescent hepatocytes accumulate in metabolic dysfunction-associated steatotic liver disease (MASLD) and are linked to worse clinical outcomes. However, their heterogeneity and lack of specific markers have made them difficult to target therapeutically. Here, we define a senescent hepatocyte gene signature (SHGS) using in vitro and in vivo models and show that it tracks with MASLD progression/regression across mouse models and large human cohorts. Single-nucleus RNA-sequencing and functional studies reveal that SHGS+ hepatocytes originate from p21+ cells, lose key liver functions and release factors that drive disease progression. One such factor, GDF15, increases in circulation alongside SHGS+ burden and disease progression. Through chemical screening, we identify senolytics that selectively eliminate SHGS+ hepatocytes and improve MASLD in male mice. Notably, SHGS enrichment also correlates with dysfunction in other organs. These findings establish SHGS+ hepatocytes as key drivers of MASLD and highlight a potential therapeutic strategy for targeting senescent cells in liver disease and beyond.